2013
DOI: 10.1002/2013gl057895
|View full text |Cite
|
Sign up to set email alerts
|

Rapid modification of cloud‐nucleating ability of aerosols by biogenic emissions

Abstract: [1] Although secondary organic aerosol formation is well studied, the extent to which oxidation products of biogenic volatile organic compounds condense onto primary aerosols and modify their cloud-nucleating properties remains highly uncertain. Here we show that water-soluble organic acids produced from the reaction between α-pinene and ozone rapidly accumulate onto preexisting particles forming coatings of organic materials that reach a mass fraction of 80-90% within a time period of 30 to 60 min for the rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
50
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 44 publications
(55 citation statements)
references
References 58 publications
5
50
0
Order By: Relevance
“…As discussed in Sect. 3.2, α-dicarbonyls are likely the most dominant products from the OH-initiated oxidation of m-xylene (Zhao et al, 2005), while organic acids are likely the dominant SOA components derived from ozonolysis of α-pinene (Ma et al, 2013). This is consistent with the higher NOC content in the total SOA mass from the OH oxidation of m-xylene as shown in Fig.…”
Section: Contribution Of Noc To Soasupporting
confidence: 79%
See 2 more Smart Citations
“…As discussed in Sect. 3.2, α-dicarbonyls are likely the most dominant products from the OH-initiated oxidation of m-xylene (Zhao et al, 2005), while organic acids are likely the dominant SOA components derived from ozonolysis of α-pinene (Ma et al, 2013). This is consistent with the higher NOC content in the total SOA mass from the OH oxidation of m-xylene as shown in Fig.…”
Section: Contribution Of Noc To Soasupporting
confidence: 79%
“…The POZ undergoes a unimolecular isomerization to produce Criegee intermediates (CIs), which subsequently yield both gas-phase and particle-phase compounds containing hydroxyl, carbonyl and acidic functional groups Yu et al, 1999). In particular, previous work has found that organic acids are the dominant SOA component (Ma et al, 2013). The OH initialed oxidation mechanism of m-xylene is more complex as described by the Master Chemical Mechanism MCM3.1 (Bloss et al, 2005); however it also leads to particle-phase acids and carbonyls (Loza et al, 2012).…”
Section: Potential Mechanisms Contributing To Observed Nocmentioning
confidence: 99%
See 1 more Smart Citation
“…Not accounting for non-ideal interactions between particle components (i.e., assuming equilibrium partitioning to an ideal solution under circumstances in which this assumption is not valid) can result in a 10-40 % overprediction of cloud droplet number, depending on aerosol loading (Nenes et al, 2001). On the other hand, the presence of surface-active organic components can contribute to enhancements in CCN activity by reducing the surface tension of the particle surface-air interface (Ma et al, 2013;Sareen et al, 2013;Woo et al, 2013). In addition, simultaneous condensation of semivolatile organic vapors and water onto aerosol particles may enhance water uptake by increasing the availability of soluble material (Topping and McFiggans, 2012;Topping et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…This implies that the influence that a high content of sulfur in fuel, particularly in China, exalts on soot properties may significantly affect the resulting atmospheric impacts and the further transformation of soot. Although the cloudforming potential of soot particles is mainly determined by their atmospheric aging Ma et al, 2013b), lean flame soot particles generated from high sulfur content fuel are coated with more sulfate species, which will increase the hygroscopicity and to some extent enhance the cloud-forming potential of soot particles . Sulfate species coating and the subsequently enhanced hygroscopicity of soot particles increase the light absorption and scattering of soot particles , and then deteriorate the visibility and the local air quality.…”
Section: Discussionmentioning
confidence: 99%